World Trade Model : Revised Estimates. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper presents updated and revised estimates for the World Trade Model. The model estimates import and export price and volume relationships for each of three types of merchandise trade--manufactured, raw material, and agricultural--for 14 of the largest industrial countries. The extended data set has generally resulted in estimated price and volume equations that fit the data better than previous versions of the model. In addition, the simulation properties of the model have been enhanced by imposing long-run activity elasticities of unity on the activity terms in the demand for imported manufactures equations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet